MAKNA MODALITAS OSORE GA ARU - Riska Satiti; Arza Aibonotika; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the meaning of epistemic modality. The purpose of this study is to explain the meaning of modality osore ga aru. The data is a corpus taken from the website ejje.weblio.jp. This is a qualitative research with a descriptive approach. Data analysis used the distribution method and the immediate constituent. It has been found that osore ga aru can include the meaning of 'possibility' which serves to express conjecture concerns or fears based on the speaker's conclusion, express conjecture concerns or fears based on the speaker's beliefs, express conjecture concerns or fears from a situation and conclude it, express conjecture concerns or the speaker's fear of the subject's actions.Key Words: Epistemic Modality, Meaning, Possibility